2011
DOI: 10.1111/j.1600-0714.2011.01026.x
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant expression of p53, p16INK4a and Ki-67 as basic biomarker for malignant progression of oral leukoplakias

Abstract: We propose the combined p53/p16(INK4a)/Ki-67 alteration as a basic marker to define high risk leukoplakia patients. Lesions not showing this alteration appear to be harmless. Future studies should validate these findings and search for proteins which can further improve the PPV of the proposed basic marker.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
49
3
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 27 publications
8
49
3
8
Order By: Relevance
“…21,22,23 In 11 premalignant cases, p53 positivity was found in 72.72% cases with an increase in suprabasal positivity as the grade of dysplasia increased. Such pattern of staining was also observed by Cruz et al, 24,25 Kerdpon et al, 26 Vered et al 27 and Nasser et al 28 These investigators also found that the p53 expression pattern was significantly related to the development of carcinoma. No statistical significance was found between histological grades, possibly due to small number of cases studied.…”
Section: Discussionsupporting
confidence: 69%
“…21,22,23 In 11 premalignant cases, p53 positivity was found in 72.72% cases with an increase in suprabasal positivity as the grade of dysplasia increased. Such pattern of staining was also observed by Cruz et al, 24,25 Kerdpon et al, 26 Vered et al 27 and Nasser et al 28 These investigators also found that the p53 expression pattern was significantly related to the development of carcinoma. No statistical significance was found between histological grades, possibly due to small number of cases studied.…”
Section: Discussionsupporting
confidence: 69%
“…The p53 protein is essential in protecting the cells against DNA damage induced directly and indirectly by UV radiation [1,12,18]. Immunohistochemical expression of p53 is largely accepted as a marker of malignant transformation, and its overexpression has been associated with malignant potential in potentially malignant lesions of the head and neck [23,24]. In the current study, p53 was present in AC, being slightly higher in AC with moderate/severe dysplasia group than in the no/mild dysplasia one.…”
Section: Discussionmentioning
confidence: 54%
“…Numerous studies have compared the biological properties of premalignant lesions with their malignant potential; to this end, the expression of some biomarkers in oral precancerous and cancerous lesions have been compared. 6,23,[25][26][27][28] The molecular events that cause a premalignant lesion to turn into a carcinoma are still unknown, and it is still impossible to predict which premalignant lesion will progress to carcinoma. 29 …”
Section: Resultsmentioning
confidence: 99%